Religion on Our Campuses - Edwards, Mark U. author. aut Link
X, 206 p.
Keywords: What is the appropriate role of religion in scholarship and teaching? Covering topics ranging from religious influences in faculty lives to questions of academic freedom, proselytization, and appropriate limits to religious expression within the Academy, this book seeks to promote faculty self-awareness and encourage dialogue with colleagues.